Forever in blue the fourth summer of the Sisterhood - Brashares, Ann. (New York Delacorte Press, 2007)
As their lives take them in different directions, Lena, Tibby, Carmen, and Bridget discover many more things about themselves and the importance of their relationship with each other.
UCWS-3213g donated by Adrienne Maguddayao - May 2018
Keywords: Best friends -- Fiction; Friendship -- Fiction; Jeans (Clothing) -- Fiction; Conduct of life -- Fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Jeans (Clothing) -- Juvenile fiction; Conduct of life -- Juvenile fiction